The Pink Tax in Consumer Behavior for Personal Care Products - Pramesti, Adenia Naura (Integrasi Sains Media, 2024)
Pricing significantly influences consumer decisions, with variations often observed for similar products due to purchase timing, market segments, and Gender. This phenomenon, known as price discrimination, can raise ethical concerns, especially when it exacerbates inequalities. A notable example is the